Leadership handbook of management and administration - Berkley, James D., ed. (Grand Rapids, Michigan : Baker Books, 1994)
This substantial resource offers pastors and church leaders practical insight into the daily issues of running a church. Conceived and compiled by the editors of Leadership journal, this book covers the full spectrum of ministry practice. Readers will learn about perennial topics such as time management, negotiating the terms of a call, handling crisis and conflict, hiring and managing staff, conducting special fund drives, spending church money, and dealing with tax and law considerations. This revised and expanded edition of a proven ministry resource contains new contributions from prominent ministry leaders. Contributors include Leith Anderson, Rick Warren, Brian McLaren, Luis Palau, John Ortberg, Aubrey Malphurs, and many others.
pt. 7. The purpose of Stewardship / Richard B. Cunningham --Planning stewardship / Victor D. Pentz --Conducting special fund drives / Ann Rauvola Bailey --Receiving and recording money / Mack Tennyson --Managing and apportioning money / Gary Fenton --Spending church money / Daniel D. Busby --Tax and law considerations / Richard R. Hammar.
Keywords: Church management